2012
DOI: 10.1017/s1368980012001255
|View full text |Cite
|
Sign up to set email alerts
|

Stocking characteristics and perceived increases in sales among small food store managers/owners associated with the introduction of new food products approved by the Special Supplemental Nutrition Program for Women, Infants, and Children

Abstract: ObjectiveThe present study assessed the impact of the 2009 food packages mandated by the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) on perceived sales, product selection and stocking habits of small, WIC-authorized food stores.DesignA cross-sectional study involving in-depth interviews with store managers/owners.SettingSmall, WIC-authorized food stores in eight major cities in the USA.SubjectsFifty-two store managers/owners who had at least 1 year of experience in the store p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(50 citation statements)
references
References 10 publications
1
47
1
1
Order By: Relevance
“…Selection decisions on healthier foods by retailers in terms of profitability Ayala et al 2012;Bonakele and Mncube, 2012;Tsegaye, 2012;Gracia et al 2010;El-Lattief, 2011;Louw et al, 2013 Not available Not enough data to give a reasonable judgement…”
Section: Profitability For Farmers Processors and Retailers/ Competimentioning
confidence: 99%
“…Selection decisions on healthier foods by retailers in terms of profitability Ayala et al 2012;Bonakele and Mncube, 2012;Tsegaye, 2012;Gracia et al 2010;El-Lattief, 2011;Louw et al, 2013 Not available Not enough data to give a reasonable judgement…”
Section: Profitability For Farmers Processors and Retailers/ Competimentioning
confidence: 99%
“…However, the increased scores observed in Connecticut were due largely to increased availability and variety of whole-grain products, while our analysis determined that increased availability of juices/fruits and infant fruits/ vegetables in addition to cereals/grains contributed to the increased scores within small WIC stores and juices/fruits and vegetables contributed within small non-WIC stores. Other investigators have also found store owners reported increased sales of and WIC recipients reported increase home availability and consumption of some of these same items shown to have increased in the retail food environment in New Orleans after the implementation of the revised WIC food packages (29,(39)(40)(41)(42)(43) .…”
Section: Discussionmentioning
confidence: 93%
“…In a 2010 telephone survey of 52 managers of small WIC-authorized stores in eight major cities, most perceived their increased sales of fresh fruits (75%) and vegetables (69%) as due to the F&V vouchers; no changes in sales were reported for processed (canned and frozen) fruits and vegetables (Ayala et al 2012). Managers who reported a daily delivery of fruit to their stores were more likely to perceive a greater increase in sales, implying that the freshness and higher quality led WIC clientele to purchase more fruit.…”
Section: Early Findingsmentioning
confidence: 99%